Pulmonary Function in Prepubescent Boys: The Influence of Passive Smoking and Sports Training - Mario Jeličić; Ognjen Uljević; Nataša Zenić (Montenegrin Sports Academy, 2017)
In this paper, we studied prepubescent boys (N = 75; 11.3 years ± 2 months) divided into three groups: two experimental groups and age-paired, non-systematically physically engaged controls (N = 25). The experimental groups consisted of 27 basketball players, and of 23 dinghy sailors. The pulmonary function was established measuring the large airway variables (inspiratory-vital-capacity, forced-vital-capacity, one-second-forced-expiratory-volume) and small airway variables (peak-expiratory-flow, and maximal-expiratory-flow after 50% and 75% exhalation). All variables were measured in absolute values and then presented and compared in relative values - predicted for age and stature. Using the simple originally constructed questionnaire, passive smoking status was observed, and the subjects were additionally sub-sampled as passive smokers, or non-exposed to passive smoking. The multivariate- analysis-of-the-variance (MANOVA) showed significant dominance (p < 0.05) of the experimental groups in the large airways variables and small airways variables, for the NS exclusively. No significant MANOVA differences were found between the basketball players and sailors, and between the non-exposed to passive smoking and passive smoking in any of the studied groups. The results of the present study indicate a positive influence of the systematic physical exercising on the pulmonary function, with no differential effects of the two-year basketball and dinghy sailing sports training on the pulmonary function.